Efficacy of Intramedullary Nailing Versus External Fixation in Treating Gustilo Type IIIA Tibiofibular Fractures (Medical Forum Monthly, 2024)
Objective: The objective of this study is to compare the clinical and functional outcomes of intramedullary nailing versus external fixation (EF) in treating Gustilo Type IIIA tibiofibular fracturesStudy Design: Randomised control trial studyPlace and Duration of Study: This study was conducted at the AIMS Hospital, Muzafarabad, from 1st March, 2024 to 1st September, 2024.Methods: Through non-probability consecutive sampling 100 patients aged above 18 years, both gender, with Gustilo Type IIIA tibiofibular fracture patients who received IMN treatment (N=51) while the remaining received EF(N=49) were included in the present study.Results: In terms of clinical outcomes, the time to union was significantly shorter in the IMN group (21.5±6.8 weeks) compared to the EF group (24.5±7.8 weeks, p = 0.02). The complication rate was notably lower in the IMN group (24%) than in the EF group (49%, p = 0.013). The infection rate was significantly lower in the IMN group, with only 6% of patients affected compared to 31% in the EF group (p = 0.002). Nonunion was observed in 4% of IMN patients versus 27% of EF patients (p = 0.003), while malunion occurred in 12% of IMN cases compared to 37% in the EF group (p = 0.001).Conclusion: Intramedullary nailing delivers superior results as an intervention approach for Gustilo Type IIIA tibiofibular fractures compared to external fixation.